Studies on foliicolous fungi-XXVIII - and DK AGARWAL, V.B. HOSAGOUOAR*, G.R. ARCHANA (Indian Phytopathology, 2007)
Four new species, namely, Asterina canthiigena, Asterostomella baliospermi, A. strombosiae and Sarcinella wrightiae are described and illustrated in detail.